Interaction Design and Children 2021
DOI: 10.1145/3459990.3465176
|View full text |Cite
|
Sign up to set email alerts
|

Learn to Machine Learn: Designing a Game Based Approach for Teaching Machine Learning to Primary and Secondary Education Students

Abstract: With the ubiquitous role of Artificial Intelligence (AI) in everyday applications such as smartphones and social media, children need digital literacy skills to navigate the digital world, critically view, and reflect on the social and ethical implications of the design and architecture of AI systems. To address this increasing need for AI literacy skills, particularly for younger students, this paper presents the rationale of the LearnML project which aims to develop a framework and game-based educational mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Besides articles focusing specifically on High School level, some courses are designed for a wider scope of educational stages, such as elementary or middle school to High School (Zimmermann-Niefield et al, 2019;Kandlhofer et al 2016;Rodríguez-Garcia et al, 2021;Voulgari et al, 2021). We also observed that some instructional units are specifically targeting girls aiming at the inclusion of minorities (Vachovsky et al, 2016).…”
Section: No Of Relevant Results (Without Duplicates)mentioning
confidence: 59%
See 4 more Smart Citations
“…Besides articles focusing specifically on High School level, some courses are designed for a wider scope of educational stages, such as elementary or middle school to High School (Zimmermann-Niefield et al, 2019;Kandlhofer et al 2016;Rodríguez-Garcia et al, 2021;Voulgari et al, 2021). We also observed that some instructional units are specifically targeting girls aiming at the inclusion of minorities (Vachovsky et al, 2016).…”
Section: No Of Relevant Results (Without Duplicates)mentioning
confidence: 59%
“…(Norouzi et A workshop aligned with the K-12 AI curriculum from (Van Brummelen 2019), in which students develop conversational agents using an interface in MIT App Inventor. (Voulgari et al, 2021) ArtBot: a game-based approach for teaching Machine Learning to primary and secondary education students.…”
Section: No Of Relevant Results (Without Duplicates)mentioning
confidence: 99%
See 3 more Smart Citations